Acúmulo de biomassa, de nutrientes e de sacarose por duas variedades de cana-de-açúcar, influenciados por doses de fósforo - Calheiros, Altanys Silva (2008)
In Brazil, the sugarcane normally is used for the production of sugar, alcohol and animal feeding. In most Brazilian soils, the phosphorus level does not assure satisfactory cultural growth, therefore, there is the necessity of supplying it in fertilization. The phosphorus is an important element in the nutrition and in the metabolism of the sugarcane and, its answer to the phosphorous fertilization is dependant of genetic and environmental factors; however, there are few studies on the answer of varieties currently cultivated to the phosphorous fertilization. Because of this scarcity of information, the reply of the RB867515 and RB92579 varieties to the phosphorous fertilization in the sugarcane-plant cycle and the first resprouting were evaluated in this present study. The research was conducted in experimental area of the Agrarian Science Center of the Federal University of Alagoas, having planted the sugarcane on September 9, 2005. The experiment, a 2 x 6 factorial, was constituted of two sugarcane varieties, six doses of phosphorus: zero, 30, 60, 90, 120 and 150 kg ha-1 of P, having triple super-phosphate as the source of P. Nitrogen fertilization, potassium with micronutrients in doses equivalent to 100; 200; 6.0; 6.0 and 7.0 kg ha-1 of N, K, Cu, Mn and Zn, were also used respectively. The treatments were distributed in blocks at random with five repetitions. In December 2006, sixteen months after having been planted, the sugarcane-plant was cut and the accumulation of dry substance, the production of sucrose and the nutritional quality of the fodder were quantified. In April of the following year, the beginning of the rainy season, the first resprouting were fertilized applying 120; 150; 5.0; 5.0 and 5.0 kg ha-1 of N, K, Cu, Mn and Zn, respectively. In the resprouting's phase of maximum growth, its nutritional state was evaluated, and in December, the sugarcane was cut to quantify the apparent production of sucrose and the accumulations of dry substance, of nitrogen, phosphorus and potassium. In the sugarcane-plant cycle the accumulations of dry substance, sucrose, phosphorus and raw protein were influenced by the phosphorous fertilization; however, the nutritional quality of the sugarcane was not significantly modified by the fertilization. In the first resprouting, the doses of phosphorus did not influence the nutritional state of the plants, verifying then, however and variety effect. Over all, nutritional deficiency of K, S, Zn, Cu and B was evidenced in the two varieties. The accumulations of dry substance, industrialized stem, apparent sucrose and of the nutrients N, P and K were not influenced by the variety. On the other hand, there was an effect of the phosphorous fertilization on these variables.